Agro-morphological variability of rice species collected from Niger - Sow, M; Sido, A.; Laing, M.; Ndjiondjop, M.N. (Cambridge University Press, 2014)
Niger harbours a wealth of diversity of Africa's rice (Oryza glaberrima) and its related wild species. We therefore engaged in a collecting mission of rice species across growing regions and agrosystems in Niger. A total of 270 rice accessions were assembled, including 177 Asian rice (O. sativa) cultivars, 67 African rice landraces (O. glaberrima), 25 O. barthii and one O. longistaminata. We found most accessions (80.7%) along the Niger River and its tributary the Dallol Maouri. Many of the accessions, except those belonging to the wild O. barthii initially found around the Lake Chad region, were also collected along the Niger River. Drought, insects, birds, rice yellow mottle virus and bacterial blight were noted as major constraints on rice production. Accession naming by farmers was consistent within regions but seldom across regions. Based on the recorded agro-morphological traits, the germplasm was classified into three clusters: (1) O. longistaminata with floating African landraces and late-maturing floating Asian rice; (2) lowland O. barthii and African landraces; (3) a mixture of irrigated Asian rice with lowland accessions of both cultivated species. The phenotypic variability of the germplasm collection, as measured by the Shannon–Weaver diversity index, was relatively high (H′ = 0.69), with accessions in the irrigated agrosystem being less diverse than those in the traditional agrosystems. There was no significant difference in the magnitude of diversity between the main eco-geographical zones and between the clusters. However, some traits contributing the most to this diversity were different. This study suggested a substantial germplasm exchange between regions in Niger.